Closing Ranks: Organized Labor and Immigration - Carlo Medici (CESifo GmbH, 2024)
This paper shows that immigration fostered the emergence of organized labor in the United States. I digitize archival data to construct the first county-level dataset on historical U.S. union membership and use a shift-share instrument to isolate a plausibly exogenous shock to the labor supply induced by immigration, between 1900 and 1920. Counties with higher immigration experienced an increase in the probability of having labor unions, the number of union branches, the share of unionized workers, and the number of union members per branch. This increase occurred more prominently among skilled workers, particularly in counties more exposed to labor competition from immigrants, and in areas with less favorable attitudes towards immigration. Taken together, these results are consistent with existing workers forming and joining labor unions for economic as well as social motivations. The findings highlight a novel driver of unionization in the early 20th-century United States: in the absence of immigration, the average share of unionized workers during this period would have been 22% lower. The results also identify an unexplored consequence of immigration: the development of institutions aimed at protecting workers' status in the labor market, with effects that continue into the present.
Keywords: J15; J50; J70; N31; N32; P10; 330; labor unions; immigration; labor market competition; discrimination